Mean Deviation Coupling Control for Multimotor System via Global Fast Terminal Sliding Mode Control - Changlin Zhu; Qunzhang Tu; Chengming Jiang; Ming Pan; Hao Huang; Zhiwen Tu (Advances in Mathematical Physics)
In view of the shortcomings of the existing multimotor synchronous control strategy, a new method of mean deviation coupling control for multimotor system via global fast terminal sliding mode control is proposed. Firstly, the mathematical model of permanent magnet synchronous motor (PMSM) under a d-q reference frame is established. Next, based on the deviation coupling control, the deviation is calculated by the average speed, and the structure of the deviation coupling control strategy is optimized. The speed controller of the multimotor system is designed based on the global fast terminal sliding mode control (GFTSMC) algorithm to improve the synchronization accuracy of the system. In addition, a load torque Luenberger observer is designed to observe the load in real time. Then, the stability analysis of the controller is carried out by using the Lyapunov function. Finally, a four-motor experimental platform is built to verify the effectiveness of the proposed control strategy.